Deep Inspiration Breath Hold: Techniques and Advantages for Cardiac Sparing During Breast Cancer Irradiation - Bergom, Carmen; Currey, Adam; Desai, Nina; Tai, An; Strauss, Jonathan B. (Frontiers in Oncology, 2018)
Historically, heart dose from left-sided breast radiotherapy has been associated with a risk of cardiac injury. Data suggests that there is not a threshold for the deleterious effects from radiation on the heart. Over the past several years, advances in radiation delivery techniques have reduced cardiac morbidity due to treatment. Deep inspiration breath hold (DIBH) is a technique that takes advantage of a more favorable position of the heart during inspiration to minimize heart doses over a course of radiation therapy. In the accompanying review article, we outline several methods used to deliver treatment with DIBH, quantify the benefits of DIBH treatment, discuss considerations for patient selection, and identify challenges associated with DIBH techniques.